The Use of Trailer Film to Increase English Essay Writing - Euis - Meinawati; Herlin Widasiwi Setianingrum; Sufi Alawiyah; Chodidjah Chodidjah; Suwarsito Suwarsito; Viviana Lisma Lestari (AL-ISHLAH: Jurnal Pendidikan, 2021)
Essay writing has a fairly complex level of difficulty. Moreover, the online and offline learning process in the era of technological progress has directed learning activities to be carried out through technological innovation. The purpose of this study was to determine the impact of film trailers on improving English essay writing skills for students at Bina Sarana Informatika University, Jakarta. The research method uses experiments with a one-group experimental design. Participants were taken using a purposive sampling technique of as many as 50 students. The research was conducted on 3rd-semester students of the 2021-2022 academic year. The data analysis technique used essay tests and observation. Data were analyzed using a t-test. The results showed that students in the Essay Writing class experienced an increase in their ability to write English essays. There are 80% of the respondents who experienced an increase in their English essay writing test scores before and after using the film trailer learning media. In addition, the data from the t-test also showed that t-Stat t-table (-10.384 2.0095), meaning that there was a significant effect of movie trailers on English essay writing skills. The results of the study also have implications for the understanding of the teaching staff regarding the use of digital learning media or technology applications in building more innovative writing classes